Controlling the corrosion and hydrogen gas liberation inside lead-acid battery via PANI/Cu-Pp/CNTs nanocomposite coating - M. A. Deyab (Nature Portfolio, 2021)
Abstract The liberation of hydrogen gas and corrosion of negative plate (Pb) inside lead-acid batteries are the most serious threats on the battery performance. The present study focuses on the development of a new nanocomposite coating that preserves the Pb plate properties in an acidic battery electrolyte. This composite composed of polyaniline conductive polymer, Cu-Porphyrin and carbon nanotubes (PANI/Cu-Pp/CNTs). The structure and morphology of PANI/Cu-Pp/CNTs composite are detected using transmission electron microscopy (TEM), scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis. Based on the H2 gas evolution measurements and Tafels curves, the coated Pb (PANI/Cu-Pp/CNTs) has a high resistance against the liberation of hydrogen gas and corrosion. Electrochemical impedance spectroscopy (EIS) results confirm the suppression of the H2 gas evolution by using coated Pb (PANI/Cu-Pp/CNTs). The coated Pb (PANI/Cu-Pp/CNTs) increases the cycle performance of lead-acid battery compared to the Pb electrode with no composite.